EU enlargement and convergence: Does market access matter? - Annekatrin Niebuhr; Friso Schlitte (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2008)
Economic integration in Europe has been accompanied by concerns about the impact of integration on regional disparities in the EU. The purpose of this paper is to investigate the effects of the most recent EU enlargement on convergence among countries and regions in the EU27. Departing from a new economic geography framework, we focus on integration effects caused by changes in market access released by the reduction of trade impediments. Special attention is paid to the catching-up process of the new member states and the development of regional disparities within the Eastern European countries. The results point to a catching-up process of the new member states. However, at the same time regional disparities within the NMS increase. Changes in market access seem to foster these processes at the national and regional level since the Eastern European countries achieve highest growth of market potentials due to declining barriers to trade. Moreover, the more prosperous regions in Eastern Europe realize the strongest benefits. However, taking these integration effects into account does not significantly alter the findings of our convergence analysis.
Keywords: C21; F15; R12; 330; Integration; market access; EU enlargement; convergence